Assessment of healthcare delivery in the early management of bacterial meningitis in UK young infants: an observational study. Issue 8 (21st August 2017) - Okike, Ifeanyichukwu O; Ladhani, Shamez N; Anthony, Mark; Ninis, Nelly; Heath, Paul T
Abstract : Objective: To define early presenting features of bacterial meningitis in young infants in England and to review the adequacy of individual case management as compared with relevant national guidelines and an expert panel review. Design: Retrospective medical case note review and parental recall using standardised questionnaires. Setting: England and Wales. Participants: Infants aged <90 days with bacterial meningitis diagnosed between July 2010 and July 2013. Results: Of the 97 cases recruited across England and Wales, 66 (68%) were admitted from home and 31 (32%) were in hospital prior to disease onset. Almost all symptoms reported by parents appeared at the onset of the illness, with very few new symptoms appearing subsequently. Overall, 20/66 (30%) infants were assessed to have received inappropriate prehospital management. The median time from onset of first symptoms to first help was 5 hours (IQR: 2–12) and from triage to receipt of first antibiotic dose was 2.0 hours (IQR: 1.0–3.3), significantly shorter in infants with fever or seizures at presentation compared with those without (1.7 (IQR: 1.0–3.0) vs 4.2 (IQR: 1.8–6.3) hours, p=0.02). Overall, 26 (39%) infants had a poor outcome in terms of death or neurological complication; seizures at presentation was the only significant independent risk factor (OR, 7.9; 95% CI 2.3 to 207.0). For cases in hospital already, the median time from onset to first dose of antibiotics was 2.6 (IQR: 1.3–9.8) hours, and 12/31 (39%) of infants had serious neurological sequelae at hospital discharge. Hearing test was not performed in 23% and when performed delayed by ≥4 weeks in 41%. Conclusions: In young infants, the non-specific features associated with bacterial meningitis appear to show no progression from onset to admission, whereas there were small but significant differences in the proportion of infants with more specific symptoms at hospital admission compared with at the onset of the illness, highlighting the difficulties in early recognition by parents and healthcare professionals alike. A substantial proportion of infants received inappropriate prehospital and posthospital management. We propose a targeted campaign for education and harmonisation of practice with evidence-based management algorithms.